Pertumbuhan Akar Rumput Benggala (Panicum maximum) Akibat Pemberian NPK yang diinokulasi dengan Cendawan Mikoriza Arbuskula. - Bela Putra (Musamus Journal of Livestock Science, 2021)
The high application of NPK fertilizer in the development of Panicum maksimum caused damage to the soil. Arbuscular mycorrhizal fungi are biological agents that can be used as an alternative to increase soil fertility, increase the efficiency of using inorganic fertilizers, and increase the productivity of Panicum maksimum . The purpose of this study was to see the changes that occurred in the roots after application of NPK fertilizer inoculated with Arbuscula Mycorrhizal Fungus on Panicum maksimum . The method used in this study was a completely randomized design with 4 treatments and repeated 5 times. The first treatment was without the provision of NPK, the second treatment was 1.5 grams of NPK/polybag, the third treatment was 3 grams of NPK/polybag, and the fourth treatment was 4.5 grams of NPK/polybag. Each treatment was inoculated with 5 grams of Arbuscular Mycorrhizal Fungi/polybag. Parameters observed were root length, root weight, root volume, and root/shoot ratio of Panicum maksimum . The results of this study showed that the application of NPK fertilizer had a very significant effect on root length, but had no significant effect on the parameters of root weight, root volume, and the ratio of shoots/roots. It can be concluded that NPK fertilizer did not affect the growth of Panicum maksimum roots inoculated with the mycorrhizal fungus Arbuscula.